Inhibition of Photoconversion Activity in Self-Assembled ZnO-Graphene Quantum Dots Aggregated by 4-Aminophenol Used as a Linker - Lee, Kyu Seung; Park, Young Jae; Shim, Jaeho; Lim, Guh-Hwan; Yim, Sang-Youp; Seo, Jin Won; Ryu, Jae Hyoung; Son, Dong Ick (MDPI, 2020)
The aggregation of zinc oxide nanoparticles leads to an increased absorbance in the ultraviolet-visible region by an induced light scattering effect. Herein, we demonstrate the inhibition of photoconversion activity in ZnO-graphene core-shell quantum dots (QD) (ZGQDs) agglomerated by 4-aminophenol (4-AP) used as a linker. The ZnO-graphene quantum dots (QD) aggregates (ZGAs) were synthesized using a facile solvothermal process. The ZGAs revealed an increased absorbance in the wavelengths between 350 and 750 nm as compared with the ZGQDs. Against expectation, the calculated average photoluminescence lifetime of ZGAs was 7.37 ns, which was 4.65 ns longer than that of ZGQDs and was mainly due to the high contribution of a slow (tau(2), tau(3)) component by trapped carriers in the functional groups of graphene shells and 4-AP. The photoelectrochemical (PEC) cells and photodetectors (PDs) were fabricated to investigate the influence of ZGAs on the photoconversion activity. The photocurrent density of PEC cells with ZGAs was obtained as 0.04 mA/cm(2)at 0.6 V, which was approximately 3.25 times lower than that of the ZGQDs. The rate constant value of the photodegradation value of rhodamine B was also decreased by around 1.4 times. Furthermore, the photoresponsivity of the PDs with ZGAs (1.54 mu A center dot mW(-1)) was about 2.5 times as low as that of the PDs with ZGQDs (3.85 mu A center dot mW(-1)). Consequently, it suggests that the device performances could be degraded by the inhibition phenomenon of the photoconversion activity in the ZGAs due to an increase of trap sites.
Keywords: FACILE SYNTHESIS; OXIDE; PHOTOCATALYSTS; PERFORMANCE; CATALYST